2003
DOI: 10.1562/0031-8655(2003)078<0235:iaopto>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Aspects of Photodynamic Therapy of Liver Tumors in a Rat Model for Colorectal Cancer¶

Abstract: We have investigated tumor immunological effects of photodynamic therapy (PDT) of liver metastases. Livers of Wag/Rij rats were inoculated with three tumors of a syngeneic rat colon carcinoma cell line, CC531. One tumor in each rat was illuminated, with or without previous administration of the photosensitizer metatetrahydroxyphenylchlorin (mTHPC). PDT was effective in causing necrosis of tumors, but it did not affect the growth rate of nearby, nonilluminated tumors in the liver. Immunological staining of tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The use of CC531 colon carcinoma cells in tumor metastasis models has been evaluated in several studies [19][20][21][22][23][24]. It has been shown that CC531 cells injected into the vena mesocolica are a reliable tumor metastasis model.…”
Section: Discussionmentioning
confidence: 99%
“…The use of CC531 colon carcinoma cells in tumor metastasis models has been evaluated in several studies [19][20][21][22][23][24]. It has been shown that CC531 cells injected into the vena mesocolica are a reliable tumor metastasis model.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study by our group confirmed the absent effect of PDT on the growth of established tumours. In this study, we also treated one out of two CC531 liver tumours with PDT and found that however effective, this treatment did not affect growth of nearby, untreated tumours [23], nor was there influx of macrophages or lymphocytes in these tumours. Both RFA and PDT of liver tumours increased resistance to local or systemic administration of tumour cells in suspension, but did not affect established tumours.…”
Section: Discussionmentioning
confidence: 78%
“…We used a rat colon carcinoma liver metastases model, CC531. We have extensive experience with this model, which has proven to be adequately reproducible [9,[21][22][23]. RFA and PDT were applied as local therapies and for regional therapy we used HAI with melphalan [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms by which PDT can destroy tumors include (i) direct tumor cell killing 256 ; (ii) ROS-induced damage to the vascular system and deprivation of nutrients and oxygen to tumors 257,258 and (iii) immunosuppressive effects on the tumor. 259,260 Some of the most commonly used photosensitizing agents include porphyrins, chlorins and phthalocyanines. 261 Many photosensitizers exhibit poor solubility in water, which limits their application.…”
Section: Light-sensitive Micellesmentioning
confidence: 99%